2013
DOI: 10.1530/eje-12-0943
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive iodine in the treatment of medullary thyroid carcinoma: a controlled multicenter study

Abstract: Objective: Radioactive iodine (RAI) therapy in medullary thyroid carcinoma (MTC) is applied in some centers, based on the assumption that cross-irradiation from thyroid follicular cells may be beneficial. However, no systematic studies on the effect of RAI treatment in MTC have been performed. The aim of this study was to analyze the effect of RAI treatment on survival in MTC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 25 publications
1
31
0
1
Order By: Relevance
“…In addition, a larger multiinstitutional study of RAI in patients with MTC from the Netherlands included a small subset of patients who underwent prophylactic thyroidectomies (n = 56), and found that none of the nine patients who received RAI developed biochemical or radiologic evidence of MTC, compared to 40% of those who underwent surgery alone. However, the univariate hazard ratio for disease-free survival in these patients was not statistically significant 15 . While it seems clear RAI should not play a role in the treatment of MTC, our findings and those described above suggest further investigation of its role as adjuvant preventative therapy following prophylactic thyroidectomy, weighing the long-term risks of adverse effects including leukemia 16 .…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In addition, a larger multiinstitutional study of RAI in patients with MTC from the Netherlands included a small subset of patients who underwent prophylactic thyroidectomies (n = 56), and found that none of the nine patients who received RAI developed biochemical or radiologic evidence of MTC, compared to 40% of those who underwent surgery alone. However, the univariate hazard ratio for disease-free survival in these patients was not statistically significant 15 . While it seems clear RAI should not play a role in the treatment of MTC, our findings and those described above suggest further investigation of its role as adjuvant preventative therapy following prophylactic thyroidectomy, weighing the long-term risks of adverse effects including leukemia 16 .…”
Section: Discussionmentioning
confidence: 67%
“…Historically RAI was considered postoperatively in patients with MTC for the theoretical “bystander effect,” which hypothesized that radioactive iodine taken up by thyroid follicular cells would prove toxic to adjacent C cells via β-ray emission. There have been some case reports and small series reporting decreased calcitonin levels in patients with known MTC treated with RAI, in addition to decreased CCH following RAI in animal studies 8-11 ; however, other series have not shown an improvement in outcomes, and a survival benefit has never been demonstrated 12-15 . One recent small study of patients with documented MTC showed a decrease in postoperatively elevated basal and stimulated calcitonin levels after RAI administration in three out of seven treated patients, all of whom had no evidence of lymph node or distant metastases 10 .…”
Section: Discussionmentioning
confidence: 99%
“…131,132 This is attributed to the fact that MTC arises from parafollicular C cells of the thyroid gland, which do not concentrate iodine. 131,132 This is attributed to the fact that MTC arises from parafollicular C cells of the thyroid gland, which do not concentrate iodine.…”
Section: Radionuclide Therapymentioning
confidence: 99%
“…If metastases are large and located in areas that are easy to remove, they should be removed surgically Discussion [5,6]. Other treatment options, such as radiation treatment, chemotherapy and embolization, are applied for patients for whom surgery is not an option [7,8].…”
Section: Case Presentationmentioning
confidence: 99%